User embracement and risk classification at obstetric emergency: evaluating operationalization in a maternity hospital school - Maria das Neves Figueiroa (Escola Anna Nery, 2017)
Abstract Objective: To evaluate the functioning of a user embracement and risk classification service in a maternity hospital school in Recife, Pernambuco, Brazil. Method: Observational, cross-sectional, and analytical study with a quantitative approach, conducted at the "Amaury de Medeiros" Integrated Health Center of the University of Pernambuco (CISAM/UPE), in April and May 2015. The sample consisted of 377 female users and 6 nurses, with the application of Stork Network's user embracement and risk classification protocol. Results: The waiting time according to risk classification was 21.2 min; the duration time was 5 min; the waiting time according to the red priority was 3.5 min. The spontaneous demand showed that 56% of the users were classified as green priority, 60% of the users reported dissatisfaction, and 33% of the nurses received training. Conclusions: The service under analysis needs agreements and assessments to promote coping strategies.